Job exhaustion among assigned and self-initiated expatriates – the role of effort and reward - Mäkelä, Liisa; Suutari, Vesa; Rajala, Anni; Brewster, Chris (Emerald, 2022)
Purpose This study explores whether expatriation type (assigned expatriates (AEs) versus self-initiated expatriates (SIEs)) is linked to job exhaustion via possible differences in required efforts for their jobs and the rewards they gain from them, and/or the balance between efforts and rewards. Adopting effort–reward imbalance (ERI) and job demands/resources (JD-R) theories, the authors study the possible role of ERI as a mediator between expatriation type and job exhaustion. Design/methodology/approach An online survey was carried out in co-operation with two Finnish trade unions, providing representative data from 484 assigned and SIEs. The authors test this study’s hypotheses through latent structural equation modelling, and the analysis was conducted with Stata 17.0 software. Findings The results show that ERI between them are correlated with the job exhaustion of expatriates in general and there are no direct links between expatriation type and job exhaustion. The required effort from AEs was higher than that from SIEs though no difference was found for rewards, and the match between effort demands and rewards is less favourable for AEs than SIEs. AEs experienced higher job exhaustion than SIEs because of the higher effort demands and greater imbalance between efforts and rewards. Originality/value The study examines the work well-being of two types of expatriates and explores the underlying mechanisms that may explain why they may differ from each other.
Keywords: Assigned expatriates; Effort–reward imbalance; Job demands-resources; Job exhaustion; Self-initiated expatriates; fi=Henkilöstöjohtaminen|en=Human Resource Management|; fi=Strateginen johtaminen|en=Strategic Management|